SELF-TESTING OF BLOOD PRESSURE ACCORDING TO THE DEPISTHTA® PROTOCOL IN THE POPULATION OF THE FRENCH LEAGUE AGAINST HYPERTENSION SURVEY 2019. (April 2021) - Girerd, X.; Pathak, A.; Vaïsse, B.; Hanon, O.
Abstract : ABSTRACT: Objective: The FLAHS 2019 survey was organized to determine the distribution of blood pressure in the adult population over 35 years of age through the use of self-screening. Design and method: FLAHS surveys are conducted by a self-administered questionnaire sent by mail to individuals from the Kantar Health Metascope permanent sampling frame (panel representing the population living in metropolitan France). Among the positive respondents to the question: Do you have a device to measure blood pressure at home? It was obtained measurements according to the depistHTA® protocol (3 consecutive measurements leaving an interval of 1 minute between each measurement while keeping the sitting position, without getting up between each measurement). The average of the last 2 measurements was taken to define the subject's BP. Results: Of the 7627 subjects aged 35 and over, 1706 had a blood pressure monitor. Self-testing was possible in 50% of subjects taking antihypertensive treatments (938 subjects) and 15% of untreated patients (767 subjects). Among the untreated: 18.8% had BP > = 140 or 90; 29.1% had BP > = 135 or 85 and 64.9% had BP > = 120 or 80. Among subjects taking antihypertensive drugs: 64.1% had BP < 140 and 90; 50.4% had BP < 135 and 85 and 14.6% had BP < 120 and 80. Among untreated people aged 35 to 54 years: 16.1% had BP > = 140 or 90; 25.7% had BP > = 135 or 85 and 59.2% had BP > = 120 or 80. Among those treated with antihypertensive drugs and aged 35 to 54 years: 68.5% had BP < 140 and 90; 54.8% had BP < 135 and 85 and 25.0% had BP < 120 and 80. Conclusions: Self-screening for blood pressure is possible in the general population. When the depistHTA® protocol is used, BP > = 140 or 90 is observed in 18.8% of untreated subjects aged 35 and over, or 5 million subjects in metropolitan France. In treated hypertensive patients, BP < 135 and 85 is noted in 50.4% of patients, indicating that control of treated hypertension is not improving in France. depistHTA® is available on stores.